2008
DOI: 10.1111/j.1440-1681.2008.04981.x
|View full text |Cite
|
Sign up to set email alerts
|

INHIBITION OF LEFT VENTRICULAR REMODELLING IN SPONTANEOUSLY HYPERTENSIVE RATS by Gαq‐PROTEIN CARBOXYL TERMINUS IMITATION POLYPEPTIDE GCIP‐27 IS NOT ENTIRELY DEPENDENT ON BLOOD PRESSURE

Abstract: 1. The present study investigated the therapeutic effects of both single and combination treatment with Yunke (technetium-99 conjugated with methylene diphosphonate; (99)Tc-MDP) and colloidal chromic phosphate (32)P (phosphonium-32) in rats with adjuvant arthritis (AA). 2. Rats were randomly allocated to one of five groups: (i) normal control group (sham operated and treated with normal saline); (ii) AA control group (arthritis induced with adjuvant and treated with normal saline); (iii) (32)P colloid group (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Additionally, it has been shown that GCIP-27 was superior at inhibiting ventricular remodeling compared with losartan [ 17 ]. In the present study, B-mode and M-mode echocardiography revealed that GCIP-27 was able to improve heart function.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, it has been shown that GCIP-27 was superior at inhibiting ventricular remodeling compared with losartan [ 17 ]. In the present study, B-mode and M-mode echocardiography revealed that GCIP-27 was able to improve heart function.…”
Section: Discussionmentioning
confidence: 99%
“…After 10 weeks of treatment (described above), all of the rats that survived were subjected to echocardiography measurements [ 17 , 23 ] under anesthesia with chloral hydrate (350 mg/kg, ip). Transthoracic two-dimensional and M-mode images were performed in animals using a Vivid 7 Echo machine with the 14 MHz probe (GE Medical Systems, Minneapolis, MN).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…SBP, DBP and HR were digitized automatically by the system after the tails were pressurized through the cuff. The final values were obtained by averaging 5 or 6 successful readings [22,23] .…”
Section: Blood Pressure Measurementmentioning
confidence: 99%